Development of a web application to evaluate agricultural crops through the MAP method - Vásquez García, Adela; Sangerman- Jarquín, Dora Ma.; Reyes Muro, Luis (Revista Mexicana de Ciencias Agrícolas, 2017)
A web application was developed, with a friendly interface, a flexible and secure database for information management, this application evaluates agricultural crops through the methodology of the matrix of policy analysis (MAP) developed by Monke and Pearson (1984). In order to know the accuracy of the web application in agricultural crops, an essay was made capturing a wheat production crop in Guanajuato (District 005 Cortazar), based on information already obtained. Once the analysis was done, it was concluded that the developed web application is efficient, accurate and reliable to evaluate agricultural crops through variables such as competitiveness, comparative advantage and protection coeffi cients. The contribution of this work shows that it is possible to create web applications that allow the evaluation of agricultural crops.
Keywords: comparative advantage, competitiveness, indicators, subsidy.